Предмет: Алгебра,
автор: misytruwsijdd
Упростите выражение: x^2-6x-9/x-3
ragimovruslan999top:
Незнаю
Ответы
Автор ответа:
0
при делении дробь переворачиваем и будет умножение
(x-3) *(x+3)/(x-3)²=
=(x-3)*(x+3) разделить на
(x-3)² сокращаем на х-3
= (x+3)/(x-3)=(-21+3)/(-21-3)=
= -18/ -24= 0.75
(x-3) *(x+3)/(x-3)²=
=(x-3)*(x+3) разделить на
(x-3)² сокращаем на х-3
= (x+3)/(x-3)=(-21+3)/(-21-3)=
= -18/ -24= 0.75
Автор ответа:
1
Ответ:
x^2-6x-9/x-3
x^2-15x-3
Похожие вопросы
Предмет: Русский язык,
автор: SilverTigerGC
Предмет: Другие предметы,
автор: dinamileeva
Предмет: Русский язык,
автор: natakaspi
Предмет: Математика,
автор: YuzikYuzik